Modelling in mechanical engineering and mechatronics : towards autonomous intelligent software models - Avgoustinov, Nikolay (London : Springer, 2007)
"Modelling in Mechanical Engineering and Mechatronics presents a model-centred approach focusing on distributed development and use of autonomous intelligent software models, particularly the efficiency of the models, and their interaction and integration into distributed autonomous intelligent systems." "Modelling in Mechanical Engineering and Mechatronics considers the viewpoints of many different experts: the modeller, engineer, system architect, software developer, and users of the models and as such will be of interest to all these people. Moreover, it attempts to bridge the gaps between modelling, engineering, computer science, knowledge representation, software engineering, model integration, standardisation and production engineering. The aim is to instruct the reader how to efficiently stimulate sophisticated products and processes in mechanical engineering in view of their continuously increasing complexity in a modern knowledge-based society."--Jacket.
Introduction Modelling Basics Conventioanl Product and Process Modelling Towards Better Product and Process Modelling Conclusion Perspectives Afterword
Includes bibliographical references and index.
Keywords: Mechanical engineering -- Computer simulation; Automatic control -- Computer simulation